Analysis of Public Service Ethics in Services at the Bogor Regency Population and Civil Registry Office - Fikoh, Windy Al; Faslah, Roni; Ikhwan, Muhammad (Jurnal Pengabdian Nusantara, 2025)
This research aims to analyze the implementation of public service ethics at the Bogor Regency Population and Civil Registry Office. This research primarily focuses on aspects of employee discipline, fairness in service, information access, and communication. The research method used is a descriptive qualitative approach with data collection techniques including interviews, observation, and documentation. The results show that there are still employees who commit ethical violations such as lack of discipline, unfair service, and suboptimal communication. The main inhibiting factors for the implementation of ethics itself are low individual moral awareness, lack of supervision, and a negative organizational culture.